137Cs concentrations in foliose lichens within Tsukuba-city as a reflection of radioactive fallout from the Fukushima Dai-ichi Nuclear Power Plant accident. (March 2015) - Ohmura, Yoshihito; Matsukura, Kimiyo; Abe, Jun-ichi P.; Hosaka, Kentaro; Tamaoki, Masanori; Dohi, Terumi; Kakishima, Makoto; Seaward, Mark R.D.
Abstract: 137 Cs concentrations in ten species of foliose lichens collected within Tsukuba-city in August 2013 ranged from 1.7 to 35 kBq/kg. The relationships between 137 Cs in two dominant species, Dirinaria applanata and Physcia orientalis, and the air dose rate (μSv/h) at the sampling sites were investigated. 137 Cs in P. orientalis measured about 1 year after the Fukushima nuclear accident was correlated ( r 2  = 0.80) more closely with the air dose rate than those measured after about 2 years ( r 2  = 0.65), possibly demonstrating its continued value as a biomonitor to reflect ambient fall-out levels. In contrast, those of Dirinaria applanata were not correlated with the air dose rate in either year. Highlights: We report 137 Cs concentrations of ten foliose lichens in Tsukuba-city, Japan. 137 Cs of Physcia orientalis correlated with the air dose rate at the sampling sites. Physcia orientalis is invaluable for monitoring the radioactive fallout.